Fecal microbiota transplantation alleviates cognitive impairment by improving gut microbiome composition and barrier function in male rats of traumatic brain injury following gas explosion - Dong, Xinwen; Su, Yaguang; Luo, Zheng; Li, Cuiying; Gao, Jie; Han, Xiaofeng; Yao, Sanqiao; Wu, Weidong; Tian, Linqiang; Bai, Yichun; Wang, Guizhi; Ren, Wenjie (Frontiers in Microbiology, 2024)
BackgroundDysbiosis of gut microbiota (GM) is intricately linked with cognitive impairment and the incidence of traumatic brain injury (TBI) in both animal models and human subjects. However, there is limited understanding of the impact and mechanisms of fecal microbiota transplantation (FMT) on brain and gut barrier function in the treatment of TBI induced by gas explosion (GE).MethodsWe have employed FMT technology to establish models of gut microbiota dysbiosis in male rats, and subsequently conducted non-targeted metabolomics and microbiota diversity analysis to explore the bacteria with potential functional roles.ResultsHematoxylin–eosin and transmission electron microscopy revealed that GE induced significant pathological damage and inflammation responses, as well as varying degrees of mitochondrial impairment in neuronal cells in the brains of rats, which was associated with cognitive decline. Furthermore, GE markedly elevated the levels of regulatory T cell (Tregs)-related factors interleukin-10, programmed death 1, and fork head box protein P3 in the brains of rats. Similar changes in these indicators were also observed in the colon; however, these alterations were reversed upon transfer of normal flora into the GE-exposed rats. Combined microbiome and metabolome analysis indicated up-regulation of Clostridium_T and Allobaculum, along with activation of fatty acid biosynthesis after FMT. Correlation network analysis indirectly suggested a causal relationship between FMT and alleviation of GE-induced TBI. FMT improved intestinal structure and up-regulated expression of tight junction proteins Claudin-1, Occludin, and ZO-1, potentially contributing to its protective effects on both brain and gut.ConclusionTransplantation of gut microbiota from healthy rats significantly enhanced cognitive function in male rats with traumatic brain injury caused by a gas explosion, through the modulation of gut microbiome composition and the improvement of both gut and brain barrier integrity via the gut-brain axis. These findings may offer a scientific foundation for potential clinical interventions targeting gas explosion-induced TBI using FMT.